2006
DOI: 10.17159/2078-516x/2006/v18i1a247
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the session RPE method for monitoring exercise training intensity

Abstract: Abstractobjective. The Session Rating of Perceived Extertion (RPE) is a method of measuring exercise intensity that may be useful for the quantitative assessment of exercise training programmes. However, there are inadequate data regarding the validity and reliability of the Session RPE method. This study was designed to evaluate both the validity and reliability of the Session RPE method in comparison to objective measures (%HRpeak, %HRreserve and %VO2peak) of exercise intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 17 publications
7
63
0
8
Order By: Relevance
“…Focusing on endurance athletes, training dose can be measured in terms of external work executed (distance, power, velocity) [1][2] , or internal physiological responses elicited by that work (heart rate, blood lactate, VO 2 ) [3][4][5][6][7][8][9][10][11][12][13] . Training dose can also be measured by how the stimulus was perceived (session RPE) 12,[14][15][16][17][18] . Most high-level endurance athletes maintain a training diary where they report their training.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on endurance athletes, training dose can be measured in terms of external work executed (distance, power, velocity) [1][2] , or internal physiological responses elicited by that work (heart rate, blood lactate, VO 2 ) [3][4][5][6][7][8][9][10][11][12][13] . Training dose can also be measured by how the stimulus was perceived (session RPE) 12,[14][15][16][17][18] . Most high-level endurance athletes maintain a training diary where they report their training.…”
Section: Introductionmentioning
confidence: 99%
“…Session RPE has already been shown to be a valid in terms of evaluating exercise intensity and monitoring training load in a number of published literature papers [20][21][22]24]. Session RPE method is not only reliable during repeat challenge by the same exercise stimulus, but is also well related to widely accepted objective measures of exercise training intensity [29]. sRPE is a valid and reliable measure of momentary exercise intensity [8,9] and reliable to calculate/measure training load.…”
Section: Discussionmentioning
confidence: 99%
“…It is moderated by i) psychological factors -among which are cognition, memory and understanding of the task; and ii) situational factors -which include knowledge of the duration and temporal characteristics of the task (e.g., continuous, intermittent or spasmodic) and knowledge of the target distance or total amount of work to be completed. Perceptual instruments have been used during and after exercise and it has been shown that the estimation-production paradigm supports the use of in-task RPE for prescribing, regulating, and assessing exercise intensity [29]. However, there are several factors that can affect the accuracy of this rating, like athlete's experience, cognition, and memory [18].…”
Section: Training Impulse the Trimp Methodsmentioning
confidence: 99%
“…At the end of each training session, participants were asked to report an overall session RPE (Herman et al 2006) using a 10 point RPE scale (Borg 1982) as established by previous studies (Foster et al 2001;Little et al 2011;Hazell et al 2014). This is a separate scale from the Borg 20 point scale that was used during VO 2peak measurement.…”
Section: Session Rpementioning
confidence: 99%